Mesozoic-Cenozoic Topographic Evolution of the South Tianshan (NW China): Insights from Detrital Apatite Geo-Thermochronological and Geochemical Analyses - Dunfeng Xiang; Zhiyong Zhang; David Chew; Marc Jolivet; Marco G. Malusà; Chao Guo; Nan Wang; Wenjiao Xiao (Lithosphere, 2023)
The present-day topography of Tianshan is the product of repeated phases of Meso-Cenozoic intracontinental deformation and reactivation, whereas the long-term Mesozoic topographic evolution and the timing of the onset of Cenozoic deformation remain debated. New insights into the Meso-Cenozoic geodynamic evolution and related basin-range interactions in the Tianshan were obtained based on new detrital single-grain apatite U-Pb, fission-track, and trace-element provenance data from Mesozoic sedimentary sequences on the northern margin of the Tarim Basin. Detrital apatite U-Pb age data from Early-Middle Triassic clastic rocks show two prominent age populations at 500–390 Ma and 330–260 Ma, with a paucity of ages between 390 and 330 Ma, suggesting that sediment source is predominantly from the northern Tarim and South Tianshan. From the Late Triassic to Early Jurassic, the first appearance of populations in the 390–330 Ma and 260–220 age ranges indicates that the Central Tianshan-Yili Block and Western Kunlun Orogen were source regions for the northern margin of Tarim Basin. In the Cretaceous strata, south-directed paleocurrents combined with the decrease in the 390–330 Ma age population from the Central Tianshan-Yili Block imply that South Tianshan was uplifted and again became the main source region to the Baicheng-Kuqa depression during the Cretaceous. Our new apatite fission-track data from the southern Chinese Tianshan suggest that rapid cooling commenced at c. 30 Ma along the southern margin, and the Early Mesozoic strata exposed on the southern flank of the Tianshan underwent c. 4–5 km of late Cenozoic exhumation during this period. This age is approximately synchronous with the onset of exhumation/deformation not only in the whole Tianshan but also in the interior of the Tibetan Plateau and its margins. It suggests that far-field, N-directed shortening resulting from the India-Asia collision was transmitted to the Tianshan at that time.